Aplasia cutis congenita: A case report - Shekhar, Lipi; Kumble, Dhanalaksmi (Indian Journal of Case Reports, 2019)
Aplasia cutis congenita (ACC) is a congenital absence of skin most commonly involves the scalp. There is no definite etiologyavailable, but multiple causes such as intrauterine infection, fetal exposure to cocaine, heroin, alcohol or antithyroid drugs, vasculardisruption, genetic causes, syndromes, and teratogens have been suggested. Here, we report the case of a late preterm male babyweighing 1.9 kg born at 36 weeks of gestation to a third gravida mother with a previous history of one stillbirth and one baby’sdeath on day 3 of life. Multiple well-demarcated raw areas showing an absence of skin over the neck, extremities and back ofvarying diameter were seen. X-ray showed features suggestive of pyloric stenosis and ultrasound of the abdomen showed bilateralhydronephrosis. A skin biopsy showed a full-thickness absence of skin and dermal appendages in the involved areas, with dermisand epidermis ending abruptly. A final diagnosis of ACC was made based on the investigations. ACC of the trunk is less commonthan scalp, and different clinical presentations may be seen in infants with aplasia cutis.